THE ROLE OF THE JUDICIARY IN EXECUTION OF ARBITRATION AWARD IN THE ARABIAN MIDDLE EAST COUNTRIES - Emad Mohammed Al-Amaren; Ahmed M A Hamad; Omar Farouk Al Mashhour (Faculty of Law, Universitas Sebelas Maret, 2020)
Arbitration has been known since ancient times, Arbitration is an ancient system known to the ancient Greeks and Romans, and the first origins of arbitration was in the ancient Roman era. Arbitration is a legal path that seeks to resolve disputes when parties choose to deal with it. The result of the arbitration is called an arbitration award. Where this judgment is issued as a decision of rights and it is binding for opponents subject to it, and when the opponent who has the right obtained an arbitration award for his benefit, this arbitration award does not pay off the purpose of it only after the implementation of the other opponent for what it says. The issue of Execution of arbitration award is very important, and the arbitration decision includes judgment on the parties to the dispute and giving the right to another party and may also include binding the parties as if the expenses were divided between them. As for the implementation of the arbitrators award, it is only if the arbitration award has reached a certain degree of strength, so that the objection to it does not have an impact on its executive power or its enforcement, and this is with the approval of the judiciary. The role of the observer of the arbitration procedures upon the issuance of the arbitration award, in addition to that he plays an important role through the arbitration procedures from bringing a witness or bringing papers from a government agency, and from that we reach the research point where the judiciary and arbitration are connected through oversight of the arbitration award after its issuance as The judiciary determines the fate of the entire arbitration process, as it can nullify this ruling or make it enforceable